From Gamification to Funification of Exercise: Case Zombie Run Pori 2015 - Friman Usva; Turtiainen; Riikka (Finland, 2022)
In this paper, we approach the topic of gamification of exercise in the context of sporting events, using a gamified running event Zombie Run Pori 2015 as our example case. We analyse the participant feedback from the event,defining its gameful and playful elements and categorising them as design-based, participant-based, or both. Our analysis shows that user experience does not directly follow from design: gameful design does not necessarily lead to gameful experiences, and gameful experiences can form without gameful design. Gamification also does not automatically guarantee more fun, motivating, or otherwise enjoyable experience. As our conclusion, we suggest that in gamification of exercise, the design process could rather be thought as funification of exercise, setting the individual user experiences and motivations as its main focus.
Proceedings of the 1st International GamiFIN Conference.